1986
DOI: 10.1002/ijc.2910370314
|View full text |Cite
|
Sign up to set email alerts
|

Multistep process of neoplastic transformation of normal human fibroblasts by 60CO gamma rays and harvey sarcoma viruses

Abstract: As reported previously (Namba et al., 1985), normal human fibroblasts were transformed by 60Co gamma-ray irradiation into immortal cells with abnormal karyotypes. These transformed cells (KMST-6), however, showed a low cloning efficiency in soft agar and no transplantability. However, upon treatment with Harvey murine sarcoma virus (Ha-MSV), the cells acquired elevated clonability in soft agar and transplantability in nude mice. Ha-MSV alone, however, did not convert normal human fibroblasts into either immort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Cooperating cellular or viral oncogenes have been shown to induce neoplastic transformation of embryonic rodent fibroblasts (12)(13)(14)(15)(16). In addition, the combined action of y-irradiation and Ha-ras oncogene has been demonstrated to produce neoplastic transformation of human fibroblasts (17). Our ability to obtain neoplastic transformation as a result of x-ray treatment of Adl2-SV40-altered human epidermal cells provides additional support for a multistep process of neoplastic conversion.…”
Section: Discussionmentioning
confidence: 94%
“…Cooperating cellular or viral oncogenes have been shown to induce neoplastic transformation of embryonic rodent fibroblasts (12)(13)(14)(15)(16). In addition, the combined action of y-irradiation and Ha-ras oncogene has been demonstrated to produce neoplastic transformation of human fibroblasts (17). Our ability to obtain neoplastic transformation as a result of x-ray treatment of Adl2-SV40-altered human epidermal cells provides additional support for a multistep process of neoplastic conversion.…”
Section: Discussionmentioning
confidence: 94%
“…Although the MSU- (19,21), who utilized KMST-6 cells. In their studies, introduction of ras oncogenes by either virus infection (18,19) or by transfection (21) resulted in cells able to form tumors in athymic mice, although, in contrast to our results with the SV40-immortalized GM0637B cells, the tumors produced with the Va2 cells did not grow progressively (18)-an important criterion for malignant transformation, along with the ability to invade.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that immortalization is a rate-limiting step in the multistage process of in vitro human cell carcinogenesis (12)(13)(14). In order to develop an immortalized cell system for studies of carcinogenesis, we have infected NHBE cells with the SV40 large T antigen gene (15).…”
Section: Oncogenesmentioning
confidence: 99%